Morgan & Mikhail's clinical anesthesiology - Butterworth, John F.; Mackey, David C.; Wasnick, John D. (McGraw-Hill, 2013)
This edition delivers a comprehensive coverage of the field's must-know basic science and clinical topics in a clear, easy-to-understand presentation. Indispensable for coursework, exam review, and as a clinical refresher, this trusted text has been extensively updated to reflect the latest research and developments.